2021
DOI: 10.1111/jre.12811
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic sequencing provides new insights into the subgingival bacteriome and aetiopathology of periodontitis

Abstract: “Open‐ended” molecular techniques such as 16S rRNA sequencing have revealed that the oral bacteriome of subgingival plaque is more diverse than originally thought. 16S rRNA analysis has demonstrated that constituents of the overall bacterial community are qualitatively similar in health and disease, differing mainly in their relative proportions with respect to each other. Species in low abundance can also act as critical species, leading to the concept of global community dysbiosis which relates to shifts in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 65 publications
(96 reference statements)
1
23
0
1
Order By: Relevance
“…As expected, the microbial composition of the different groups varied largely throughout the study. Although cross-sectional studies have found an association of individual organisms with the disease, the oral microbiome’s relative composition varies from study to study [ 31 33 ]. Our results show that the microbial communities in our samples followed oscillating patterns significantly different in the three clinical groups studied.…”
Section: Discussionmentioning
confidence: 99%
“…As expected, the microbial composition of the different groups varied largely throughout the study. Although cross-sectional studies have found an association of individual organisms with the disease, the oral microbiome’s relative composition varies from study to study [ 31 33 ]. Our results show that the microbial communities in our samples followed oscillating patterns significantly different in the three clinical groups studied.…”
Section: Discussionmentioning
confidence: 99%
“…Periodontitis follows a polymicrobial model of community dysbiosis, and the transition to disease resembles ecological succession that culminates in a higher proportion of oral pathobionts [ 42 ]. As nonresolving inflammation is thought to drive this conversion, the application of host modulation, which refers to manipulation of the immune response to prevent or ameliorate tissue damage, may facilitate an environment that reverses dysbiosis and promotes repair [ 2 ].…”
Section: Minimizing the Need For Surgerymentioning
confidence: 99%
“…To date, there are many studies that have focused on the oral microbiome in PD that use metagenomic technologies highlighted in two recent reviews [7,8]. However, most of these studies are based on 16S rRNA amplicon sequencing.…”
Section: Introductionmentioning
confidence: 99%